Dyseminacja, eksplikacja semantyki, semantyczna innowacja (Trzy koncepcje semantyki tekstu literackiego) - Horvath, Geza; Orlik, Joanna (Przestrzenie Teorii, 2007)
Dyseminacja, eksplikacja semantyki, semantyczna innowacja (Trzy koncepcje semantyki tekstu literackiego)